Effectiveness Of Mobile Health Apps and Telepsychiatry in Supporting Mental Health Nursing Care: A Systematic Review - Swati, Swati; Sharma, Suresh; Thakur, Nishtha (Journal of Neonatal Surgery, 2025)
Background: Mental health disorders are a significant global health burden, and the increasing demand for psychiatric care has intensified the need for innovative service delivery models. Mobile health (mHealth) applications and telepsychiatry have emerged as transformative tools in mental health nursing, offering accessible, cost-effective, and patient-centered interventions. However, the effectiveness of these digital tools in enhancing mental health nursing outcomes remains underexplored. Objective: This systematic review aimed to evaluate the effectiveness of mobile health applications and telepsychiatry platforms in supporting mental health nursing care across diverse populations and settings. The review synthesizes evidence on their impact on patient outcomes, therapeutic relationships, and the roles and competencies of mental health nurses. Methods: A systematic literature search was conducted using databases such as PubMed, Scopus, CINAHL, and PsycINFO for studies published between 2015 and 2024. Inclusion criteria encompassed randomized controlled trials, quasi-experimental studies, and qualitative studies focusing on the integration of mHealth apps or telepsychiatry into mental health nursing practice. Quality appraisal was performed using the Joanna Briggs Institute (JBI) critical appraisal tools. Results: Six studies met the inclusion criteria. A randomized controlled trial by Berry et al. (2018) investigated the use of a recovery-oriented mobile app (Actissist) in patients with psychosis and found significant improvements in medication adherence and self-management, with nurses playing a key role in app-facilitated care planning. Another RCT by Nicholas et al. (2022) examined a nurse-supported digital CBT app for depression and reported clinically significant symptom reduction over 12 weeks. A quasi-experimental study by Zisser et al. (2020) explored the impact of asynchronous telepsychiatry consultations on patient engagement and medication titration speed, demonstrating reduced time to treatment adjustment and increased nursing autonomy. In a qualitative study, de Girolamo et al. (2021) reported that community mental health nurses found telepsychiatry improved service continuity, though they expressed concerns about patient privacy and digital literacy. A mixed-methods study by Erlangsen et al. (2019) on suicide prevention via a nurse-moderated digital outreach platform revealed reduced suicidal ideation scores and positive nurse-patient digital alliance. Lastly, a pilot study by Manjunatha et al. (2020) in India highlighted telepsychiatry’s effectiveness in extending psychiatric nursing support to rural populations, with reduced relapse rates and increased access to care. Conclusion: The findings indicate that both mobile health applications and telepsychiatry are effective in augmenting mental health nursing care. These tools improve patient engagement, treatment adherence, and symptom control while enhancing nursing roles in education, monitoring, and care coordination. However, challenges such as data privacy, digital literacy, and system-level integration persist. Future research should focus on nurse-led digital interventions, standardized training frameworks, and policy adaptations to maximize the benefits of these technologies in mental health care..